Paracetamol induced bullous fixed drug eruptions - Kakode, Kalyani Pai; Kakode, Varun Pai (International Journal of Research in Medical Sciences, 2019)
Paracetamol is a commonly used antipyretic and analgesic with a weak anti-inflammatory action with a good safety profile in children and adults. This has resulted in its over prescription and large over the counter sale. Thus, adverse drug reactions due to paracetamol may be easily overlooked resulting in delay in diagnosis. Author present a case report of a 12 year old boy with bullous fixed drug eruptions due to paracetamol while he tolerated NSAIDS well. This highlights the need of adverse drug reaction monitoring and reporting, for early detection and prompt treatment of drug related morbidity and the cautious use of even the most commonly used drugs.